2010
DOI: 10.1103/physrevstab.13.071302
|View full text |Cite
|
Sign up to set email alerts
|

Theory of wakefields in a dielectric-filled cavity

Abstract: An analytical solution of a wakefield from a charge moving on the axis of a dielectric-filled cylindrical cavity is derived. A solution to the wakefield in a waveguide with only a boundary at the cavity entrance is already known. To take into account a boundary at the cavity exit, we introduce an imaginary antibeam, with opposite charge, which is created at the same time when the beam passes the exit boundary and continues to move along with the original beam at the same velocity. Although the beam has been an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…To compare the analytical and the simulated DWR spectrum result, we delete the longitudinal field components in the edge and interference zones according to Refs. [26][27][28], then the simulated DWR spectrum can be…”
Section: Analytical and Simulated Resultsmentioning
confidence: 99%
“…To compare the analytical and the simulated DWR spectrum result, we delete the longitudinal field components in the edge and interference zones according to Refs. [26][27][28], then the simulated DWR spectrum can be…”
Section: Analytical and Simulated Resultsmentioning
confidence: 99%
“…In this study, we neglect F wf i because the relatively short propagation distances and bunch lengths make the effect of wakefields negligible. For acceleration studies involving long propagation distances, or multiple bunches of substantial charge, wakefields should be taken into consideration by implementing formulas derived in previous studies [354]. We also neglect the radiation reaction force since the employed scheme accelerates the electrons primarily via the z-directed component of the electric field, with minimal transverse wiggling.…”
Section: Relativistic Electrodynamics In a Waveguidementioning
confidence: 99%
“…Also the computer simulation of wakefield excitation in the cylindrical dielectric resonator by the train of three bunches has been performed. The contribution of dispersion spreading and transition radiation (see [20]), excited at the input and output boundaries of the resonator, into the wakefield is taken into account. It has been shown that the dependence R=2N, which follow from the theory for Cherenkov radiation is performed approximately.…”
Section: Introductionmentioning
confidence: 99%